The Role of Starting Points to Order Investigation: Why and How to Enrich the Logic of Research Questions - William C. Bausman (Philosophy, Theory, and Practice in Biology, 2022)
What methodological approaches do research programs use to investigate the world? Elisabeth Lloyd's Logic of Research Questions (LRQ) characterizes such approaches in terms of the questions that the researchers ask and causal factors they consider. She uses the Logic of Research Questions Framework to criticize adaptationist programs in evolutionary biology for dogmatically assuming selection explanations of the traits of organisms. I argue that Lloyd's general criticism of methodological adaptationism is an artefact of the impoverished LRQ. My Ordered Factors Proposal extends the LRQ to characterize approaches with sequences of questions and factors. I highlight the importance that ordering one's investigation plays in approaches at the level of adaptationism by analyzing two research programs in community ecology: competitionists and neutralists. Competitionists and neutralists take opposed starting points and use explanatory and developmental heuristics to consider more factors in due time. On the Ordered Factors Proposal, these approaches are not only the ecological factors they are open to considering but also the order in which they will consider them. My disagreement with Lloyd's over how to characterize methodological approaches reflects different views about methodological monism and pluralism.